UJI TOKSISITAS AKUT EKSTRAK ETANOL AKAR KB (Coptosapelta tomentosa Valeton ex K.Heyne) DENGAN METODE Brine Shrimp Lethality Test (BSLT) - Risa Supriningrum; Sapri Sapri; Vici Ali Pranamala (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
The roots of KB plants (Captosapelta tomentisa) is used empiricallyby Dayak Kenyah community as a drug leukorrhea. Leukorrhea is one of the early symptoms of cervical cancer. Early methods to determine the LC50 value or toxicity of anticancer KB roots have not been reported. The aim of research is to determine the value of the toxicity of KB root. Research was conducted by an experimental study. Research stages include sample processing, extraction and acute toxicity test by Brine Shrimp Lethality Test (BSLT). BSLT testing to determine LC50 values with a concentration of 250 ppm, 300 ppm, 400 ppm, 450 ppm and a negative control. Analysis of the data used are probit analysis method. The results showed the presence of flavonoids, alkaloids and saponins in of the ethanol extract of KB root . The test results obtained acute toxicity LC50 value is 299.226 mg / ml, so that the ethanol extract of roots KB potentially toxic to the larvae of Artemia salina Leach.